The Relationship among Domestic Credit, Financial Development and Economic Growth in the Gambia - Jammeh, Ismaila Y (International Journal of Social Sciences Perspectives, 2022)
This study examines the relationship among domestic credit availability to the private sector, financial development and economic growth in the Gambia from 1967 to 2020. Financial development has been a crucial driver of economic growth by channelling funds from those with financial resources, who lack the business investment ideas to those with investment decisions but lack the resources to kick start their investment ideas. The development of this sector will not only promote economic growth but will create confidence for lenders in providing funds to investors and these funds will be monitored to ensure they’re used in productive projects to prevent defaults and financial crises. The study employed a VAR analysis to examine the relationship among these variables. However, given the lack of data on financial development, the ratio of broad money to GDP and the ratio of domestic credit to the private sector to GDP was used as a measure of financial development. The result shows that financial development has a direct impact on the changing amount of domestic credit available for the private sector. Although the availability of domestic credit to the private sector has little impact on economic growth, this seemingly small impact will significantly improve further economic growth in the Gambia. Therefore, policymakers should put more effort into developing and improving the credibility of the financial sectors in the Gambia which will create confidence in lenders and thus monitor the activities of credit borrowers if those credits are used productively.